Tofacitinib reduces acute lung injury and improves survival in a rat model of sepsis by inhibiting the JAK-STAT/NF-κB pathway - Xinxin Zhang; Xingsheng Wang; Li Sun; Guangsheng Gao; Yun Li (BMC, 2023)
Abstract Acute lung injury is a major cause of death in sepsis. Tofacitinib (TOFA), a JAK inhibitor, has anti-inflammatory activity in autoimmune diseases, but its role in acute lung injury in sepsis remains unclear. The purpose of this study is to establish a septic rat model by cecal ligation and perforation, and to evaluate the effect of tofacitinib on the survival rate of septic rat model and its role in acute lung injury in septic rats and the possible mechanism of action. In this study, TOFA (1 mg/kg, 3 mg/kg, 10 mg/kg) was used to observe the survival rate of septic rats. It was found that TOFA (10 mg/kg) significantly improved the survival rate of septic rats. We selected TOFA (10 mg/kg) and focused on the protective effect of TOFA on acute lung injury. The results confirmed that TOFA significantly inhibited the expression of TNF-α, IL-1β, IL-6 and IFN-γ inflammatory factors, reduced the W/D weight ratio of septic lung tissue, and significantly improved lung histopathological damage. These results may be related to the inhibitory effect of TOFA on JAK-STAT/NF-κ B signaling pathway. In conclusion, for the first time, we found that TOFA has a protective effect against sepsis-induced acute lung injury, and it may be a promising drug for the treatment of acute lung injury in sepsis.